1993
DOI: 10.1093/ndt/8.6.535
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling and underdialysis in CAPD patients

Abstract: Kinetic analysis was performed in all 58 patients undergoing standard CAPD. The urea distribution volume was estimated from anthropomorphic measurements (Watson formulae). Normalized protein catabolic rate (NPCR), daily protein leak (PL), urea and creatinine Kt/Vs, clearances and peritoneal mass transfer coefficients (Kp) were calculated from measurements on serum, 24-h urine and PD fluid effluent. The mean total (renal+PD) daily creatinine and urea Kt/Vs (KT/V) were 0.31 (range 0.15-0.79) and 0.31 (0.18-0.65)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…According to the literature, nPCR is directly influenced by total dialysis dose and inversely influenced by age [5, 18, 19]. In our study, RRF was the main factor related to nPCR values followed by gender (PCR normalized with distribution volume).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…According to the literature, nPCR is directly influenced by total dialysis dose and inversely influenced by age [5, 18, 19]. In our study, RRF was the main factor related to nPCR values followed by gender (PCR normalized with distribution volume).…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, the most important variations in the total dose depend mainly on different degrees of RRF. As a matter of fact, Tattersall et al [5]found a correlation of 0.79 between renal and total KT/V with no significant relationship between total KT/V and the type of peritoneal transport or daily volumes infused. In our study, RRF was the only factor related to total KT/V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the drug candidates like irbesartan, spironolactone, and irbesartan plus spironolactone were found to lower peritoneal fibrosis in rats with bacterial peritonitis [6]. Residual renal function (RRF), the measure of dialysis adequacy and creatinine clearance [7] from the kidney accounts for most of the variability in the requirement for dialysis [8]. It is the major determinant of morbidity and mortality in patients on PD [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may contribute to impaired UF, such as the type of buffer used in the dialysate, CAPD of greater than two years duration (even in the absence of peritonitis), increased exposure to dialysate glucose, and possibly diabetes mellitus and the use of b blockers. [5][6][7] b blocker drugs were reported to cause UF failure in CAPD patients. [8] In these patients, hypertension, coronary artery disease, and chronic heart failure are frequently encountered diseases that necessitate b blocker usage.…”
Section: Introductionmentioning
confidence: 99%